Pathways to Turbulent Dissipation in a Submarine Canyon - Charlotte Bellerjeau; Matthew H. Alford; Arnaud Le Boyer; Giovanni Dematteis; Alberto Naveira Garabato; Gunnar Voet; Nicole Couto; Bethan L. Wynne‐Cattanach (Geophysical Research Letters)
Abstract Velocity and turbulence observations are used to estimate the forward cascade of kinetic energy from the internal tide to dissipation within a steep canyon. Two methods for computing cross‐frequency kinetic energy flux are compared to observed dissipation. One method, coarse graining, allows strongly nonlinear dynamics while the other assumes weak nonlinearity. Fluxes from both methods agree within a factor of 3 with dissipation estimates from a finescale parameterization which is often used in climate‐scale ocean models. Coarse graining predicts 68% of energy fluxing to dissipation from frequencies lower than 8cpd, while the weakly nonlinear method predicts 34%. The weighting of energy flux toward lower frequencies supports a shorter frequency‐space pathway to dissipation in the presence of topographic wave breaking than assumed by parameterizations. Enhanced near‐boundary mixing and upwelling has implications for the rate and spatial distribution of the upwelling branch of the global overturning circulation.